2015
DOI: 10.1007/s13312-015-0588-z
|View full text |Cite
|
Sign up to set email alerts
|

Small for gestational age: Growth and puberty issues

Abstract: Being born small for gestational age predisposes to many metabolic and pubertal disorders. Special emphasis is needed for early detection and management through early surveillance in growth clinics, and regular follow-up to prevent associated comorbidities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 30 publications
2
17
0
1
Order By: Relevance
“…This effect is similar to what is found in other children born small for gestational age [25, 34] and in prematurely born children [35]. Prenatal starvation is associated with epigenetic changes that could persist throughout life, causing a tendency for energy conservation and thus overweight [36, 37].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This effect is similar to what is found in other children born small for gestational age [25, 34] and in prematurely born children [35]. Prenatal starvation is associated with epigenetic changes that could persist throughout life, causing a tendency for energy conservation and thus overweight [36, 37].…”
Section: Discussionsupporting
confidence: 79%
“…Similar results have been found in children born small for gestational age, who continue to gain excess body fat even after catch-up in weight [25]. A high waist-to-height ratio is a known risk factor for insulin resistance and metabolic syndrome [34]. As severe PE is characterized by inflammation [40, 41], and studies indicate an association between inflammatory disorders in adults and metabolic syndrome [42] one can speculate that exposure to severe PE might indirectly and via inflammation be a risk factor for metabolic syndrome.…”
Section: Discussionsupporting
confidence: 61%
“…There are two types of NBW abnormalities according to the gestational age and sex-specific INTERGROWTH-21st curves: small for gestational age (SGA; birth weight \ 10th percentile) and large for gestational age (LGA; birth weight [ 90th percentile) [1]. SGA is associated with increased newborn morbidity and mortality and an increased risk of developmental dysfunction and metabolic disease in later life [2].…”
Section: Introductionmentioning
confidence: 99%
“…The causes of death in LBW neonates include respiratory and brain immaturity, hypothermia, hypoglycemia, and infection [1]. In addition, LBW infants are at high risk of impaired growth and development [4]. A recent review of available interventions suggested that breastfeeding, hygiene, antenatal corticosteroids to prevent preterm birth complications, case management of suspected infections, and hospital care of small babies that includes Kangaroo Mother Care (KMC) are the most effective interventions for improving survival of LBW infants [5].…”
Section: Introductionmentioning
confidence: 99%